Fruit ripening and postharvest life of banana varieties at different temperatures and packaging - Bantayehu, Muluken (Journal of Postharvest Technology, 2017)
Banana (Musa accuminata and Musa balbisiana) is the fifth most important crop in world export trade after coffee, cereals, sugar and cocoa.  It is the first important fruit crop produced in Ethiopia. However, the ripening, quality and postharvest life of the fruit need to be improved to  meet domestic and international consumer preference. An experiment was conducted with the objectives to describe the banana fruit quality of  different varieties, identify optimum temperature for ripening and evaluate the efficacy of packaging material for better ripening and long  postharvest life. The result of the experiment revealed the existence of highly significant variation between fruit samples of varieties harvested  at different days, ripening temperatures, packaging, and their second and third order interaction for fruit length, fruit weight, fruit volume,  pulp/peel ratio, pulp diameter. Improved color development was achieved for banana ripened at 15oC and 20oC. The result of the experiment  depicted that better fruit quality, firmness and color development were achieved by ripening fruits with packaging than without it. Banana fruits  ripened at 15oC and 20oC with perforated plastic packaging developed better ripening quality and postharvest life. Further research on  postharvest technologies that can enable to improve ripening quality and postharvest life of Ethiopian banana at producer, wholesale and retail  level should be conducted.
Keywords: Packaging; ripening,; temperature; pulp peel ratio; postharvest life